2015
DOI: 10.1037/a0037167
|View full text |Cite
|
Sign up to set email alerts
|

Existential therapies: A meta-analysis of their effects on psychological outcomes.

Abstract: Despite the small number and low quality of studies, some existential therapies appear beneficial for certain populations. We found particular support for structured interventions incorporating psychoeducation, exercises, and discussing meaning in life directly and positively with physically ill patients. It is important to study more precisely which existential intervention works the best for which individual client.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 75 publications
(139 reference statements)
4
100
0
10
Order By: Relevance
“…This resonates well with what Ward (2006) underlines as the reality of group work in general. This is also in line with clinical Norwegian group psychotherapy as reported by Lorentzen and Ruud (2014) and with existential therapy tradition as reported by Vos et al (2015). The various group approaches identified in this study share aims and scopes with ordinary group psychotherapy and they are mainly anchored in existential and psychodynamic theory.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This resonates well with what Ward (2006) underlines as the reality of group work in general. This is also in line with clinical Norwegian group psychotherapy as reported by Lorentzen and Ruud (2014) and with existential therapy tradition as reported by Vos et al (2015). The various group approaches identified in this study share aims and scopes with ordinary group psychotherapy and they are mainly anchored in existential and psychodynamic theory.…”
Section: Discussionsupporting
confidence: 54%
“…Existential approaches are reported to exist in various practices such as counselling for persons suffering from psychotic disorders and drug abuse (Mendelowitz & Schneider, 2008;Schneider, 2011). In a recent meta-analysis on existential therapies for somatically ill patients (Vos, Craig, & Cooper, 2015), 15 randomized controlled trials were identified. Four types of outcomes were categorized: effects on positive meaning in life and improvements in symptoms, self-efficacy and physical well-being.…”
Section: Relevant Researchmentioning
confidence: 99%
“…The finding that MIL concerns were not highly associated with externalizing problems is perhaps not surprising because people are not typically reflecting as much on inner problems and experiencing when acting out. The results for physical health problems are somewhat surprising, however, because it seems like lifethreatening diseases and terminal illness often force people to take stock of their lives and figure out how they want to live before they die (Yalom, 1980), and several meaning-oriented group therapies have specifically been developed for working with clients who have physical diseases (Vos et al, 2015). It may be that the term "physical health concerns" did not completely capture the intensity involved in life-threatening diseases and terminal illnesses.…”
Section: Client Factorsmentioning
confidence: 96%
“…We generated possible consequences based on the theoretical approaches to working with MIL reviewed above, the empirical MIL literature (e.g. Flora & Stalikas, 2012;Hsiao et al, 2012;Vos et al, 2015), and the psychotherapy literature (e.g. Hill & Lambert, 2004).…”
Section: Empirical Data About Interventions For Working With Mil In Pmentioning
confidence: 99%
“…Many cancer survivors encounter physical hindrances and are confronted with psychosocial and existential problems, also years after curative treatment is completed. 1,2 There is growing evidence that meaning-focused coping is a viable way to successfully adjust to the aftermath of cancer, 2 especially if meaning can be made from the cancer experience. 3,4 Breitbart and colleagues developed meaningcentered group psychotherapy (MCGP) to improve psychological wellbeing in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%